Research hotspots and trends in healthcare workers' resilience: a bibliometric and visualized analysis - Yang, Luhuan; Li, Zifeng; Lei, Yunhong; Liu, Jinglan; Zhang, Rong; Lei, Wei; Abd Rahman, Anita (Elsevier, 2024)
Background The resilience of healthcare workers has gained increasing attention, yet comprehensive studies focusing on recent trends and developments are scarce. We conducted an extensive bibliometric analysis from inception to 2023 to address this gap. Methods Publications on healthcare workers' resilience were extracted from the Web of Science Core Collection database. Bibliometric analysis was conducted with CiteSpace, VOSviewer, and Scimago Graphica, focusing on annual publications, country/region, institution, journal, author, keyword analysis, and reference co-citation analysis related to resilience in healthcare workers. Results The analysis included 750 documents, revealing a general upward trend in publications across 67 countries/regions, 1,251 institutions, and 3,166 authors. The USA and China emerged as the top contributors, with 192 and 168 publications, respectively. Based on keyword analysis and reference co-citation analysis, the focus areas include the Resilience Scale, the impact of the COVID-19 pandemic on HCWs and their resilience, and nurse resilience. Conclusion This study highlights the growing interest in healthcare workers' resilience by using bibliometric and visualization techniques for effective analysis. This paper will enhance scholars' understanding of the dynamic evolution of healthcare workers' resilience and identify emerging research topics.